(untitled) (Research, Society and Development, 2025)
To investigate the degree of cardiac involvement caused by COVID-19 in patients when vaccines were not yet available and the cardiac sequelae by monitoring electrocardiogram (ECG) and echocardiogram (ECHO) exams between 90 and 180 days after discharge hospital, this study was carried out. Methodology: Patients admitted from July 2020 to January 2021 in the hospital’s wards and ICUs, with a positive result for COVID-19 using the RT-PCR technique, were included and underwent electrocardiogram and echocardiogram examinations during hospitalization within 3 days of hospitalization. entry and after 90 to 180 days after hospital discharge. Results: 114 patients were included, 90 of whom were discharged. The majority of those who died had comorbid hypertension (75%) and 29.6% of patients had previous heart disease. Of the surviving patients, 29 patients underwent ECG changes, and 12 patients had ECG changes upon admission. After 90 days, only 49 patients returned for an ECG and 14 had signal of alterations. Regarding the ECHO, 45 patients returned and 16 of them had an altered ECHO. In a more detailed evaluation, using ECHO strain, it was observed that 23 patients had ECHO alterations and 17 of them did not have heart disease prior to hospitalization. Conclusion: the degree of cardiac involvement in the studied population was around 30%, excluding patients who already had heart disease prior to hospitalization. These results show that COVID-19 itself may be responsible for the sequelae of cardiac injury.